Guidelines for Development and Promote Bicycle Use in Green University:Walailak University, Nakhon Si Thammarat Province - Phetkongtong, Nanaphat (Journal of Architectural/Planning Research and Studies (JARS), 2017)
Research aimed to analysis the cycling attitudes and behaviors in university area, to discover condition and limitation of physical bicycle way existing, to improve the existing bicycle way in practical use, to be guideline in term of improving a bicycle route system in the green university. This research used four different methods of data collection. The first, a literature review, the second, by analyzing existing university documents, the third, a questionnaire and finally a survey and open forum for sharing ideas and opinions. These research methods were carried out within two groups. The total of 47 staffs and 338 students were chosen through stratified random sampling. Descriptive statistics were used to analyze the data collected from the Division of land and building as well as from the questionnaires and surveys. In-depth comments were collected from knowledge sharing activity. The research found that there are four ways of improving the current system which are as follows: 1.) A set of rules or guidelines aimed at encouraging bicyclists to go in the same direction. 2.) Long term planning conducted with input from users. 3.) The new system should be designed to meet the needs of everyone. 4.) There should be a clear divided land use according to the public transit system.